التوزّع العمودي للعوالق الحيوانية وتغيّراتها المكانيّة والزمانيّة في المياه الشاطئية لمدينة جبلة - الحنون كمال; حمامة ماجد (Latakia University Journal -Biological Sciences Series, 2019)
جرت عملية الاعتيان العمودي في الفترة الممتدة بين آب 2009 وتموز2010 من محطّات بعيدة عن الشاطئ تابعة لثلاث مناطق تقع في المنطقة الشاطئيّة لمدينة جبلة، تتصف كل منطقة بخواص بيئية تجعلها مميزة عن المناطق الأخرى.و ترافق جمع العينات بقياس درجة حرارة الماء، الملوحة،الأوكسجين المنحل في الماء، والشفافية بلغ العدد الإجمالي للعينات المدروسة في جميع مناطق الدراسة 252 عينة. تمّ تحديد 29 زمرة تصنيفية، ينتمي 151 نوعاً، وجنس واحد من العوالق الحيوانية إلى 22 زمرة تصنيفية مختلفة منها، في جميع مناطق الاعتيان، وطبقاتها المائية المختلفة، خلال الفصول المختلفة . ينتمي من بين المجموع الكلي للأنواع 84 نوعاً إلى مجدافيات الأرجل Copepoda . لوحظ من خلال الدراسة أنّ معظم الأنواع والزمر التصنيفية المختلفة قد ظهرت في جميع مناطق الاعتيان، وكذلك في طبقاتها المائية المختلفة .لكنّ الطبقة المائية (100-0) م ،كانت هي الأكثر تنوّعاً، تلتها الطبقة المائية (100-50) م ،في جميع مناطق الاعتيان . تبيّن نتيجة الدراسة، أنّ هناك أنواعاً وزمراً تصنيفيةً مختلفةً، ظهرت بشكل عام في جميع الفصول ،بينما ظهرت أنواع أخرى في فصلٍ واحدٍ دون الفصول الأخرى، وأنّ أغنى الفصول هو فصل الصيف (135) نوعاً، يليه فصل الربيع (124) نوعاً . The Vertical sampling process took place in the period between August 2009 and July 2010 from stations far from the beach belonging to the three regions located in the coastal zone of the city of Jableh. Each region is characterized by environmental characteristics which make them distinct from other regions. Associated with samples collection and measurement of water temperature, salinity, dissolved oxygen in the water, and transparency. The total number of samples studied in all regions of the study sample of 252. 29 were selected taxonomic group, 151 species, and one genus of zooplankton taxonomic group belong to 22 different ones, in all areas of sampling, and different layers of water during the different seasons. Of the total number of species belonging to 84 species of Copepoda. Observed during the study that most of the species, and taxonomic different factions, have appeared in all sampling areas, as well as in the different layers of water. But the layer of water (100-0) m, it was the most diverse, followed by a layer of water (100-50) m, in all sampling areas. The Result of the study showed that there are species, and different taxonomic factions, appeared in general in all seasons, while other species appeared in one season, without the other seasons. And that the richest seasons is summer (135) species, followed by spring (124) species.